The COVID-19 pandemic and orthodontic practice in Nigeria - Isiekwe, Ikenna Gerald (J Orthod Sci, 2021)
OBJECTIVES: This study was aimed at assessing the knowledge and awareness of orthodontists and orthodontic residents in Nigeria about the COVID-19 pandemic and the appropriate infection control measures required to mitigate its spread in orthodontic practice. MATERIALS AND METHODS: It was a cross-sectional descriptive study of orthodontists and orthodontic residents. Ethical approval for the study was obtained from the Institutional Review Board. Data collection was via an online questionnaire designed using Google forms and these were sent to the phone numbers of study participants. Data analysis was done using Statistical Package for Social Sciences version 20. RESULTS: A total of 73 respondents with a mean age of 43.41 ± 9.21 years participated in the study. About 90% of the respondents had a very good knowledge of COVID-19, including its etiology, modes of transmission, signs, and symptoms. However, very few respondents were aware of the less common symptoms such as skin rash (16.4%) and red eyes (26%). Over 80% of the respondents knew the appropriate measures to take to prevent the spread of the virus in the dental clinic, in addition to the appropriate personal protective equipment (PPE) to use. CONCLUSION: The respondents had a very good knowledge of the basic epidemiology of COVID-19 and the means of prevention of its transmission in the dental clinic. However, there was limited knowledge of the less common symptoms of the infection. In addition, majority of the respondents had a very good idea of the appropriate PPE to be used.